THE TREATISE OF AT-TATHKIRA-TAL-HIRAWIYAH FI FUNUN-AL-HARBIYAH - Ali ibn Abu-Bakr al-Hirawi; Asghar Gha’edan (تاریخ اسلام)
The work before you is the translation of at-Tathkira-tal-Hirawiyah fi Funun-al-Harbiyah, a treatise written by ‘Ali ibn Abu-Bakr al-Hirawi probably in the 6th century A.H. this book has been written in twenty four chapters. Its first ten chapters are dedicated to the rules of governance and the last fourteen chapters to the rules of war. In the first ten chapters, the writer presents to the king recommendations, advices, and guidelines on how to run a country. Characteristics and qualities of ministers, courtiers, provincial governors, judges, administrators and scribes, and ambassadors and envoys of government are issues treated in brief segments here. The second part of the book is devoted to the techniques and art of war and its strategies and tactics. Here, topics such as the qualities of spies, the dispatch of intelligence agents to acquire information on the enemy, alertness, discipline and preparation in the face of enemy attack, inciting and encouraging people to war, types of battle such as opening castles and setting siege and conquering cities, and other war techniques that a sultan or caliph should know concerning the rules and musts of war have been discussed and reviewed.